2021
DOI: 10.1038/s41598-021-82688-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repetition on the behavioral and neuronal responses to ambiguous Necker cube images

Abstract: A repeated presentation of an item facilitates its subsequent detection or identification, a phenomenon of priming. Priming may involve different types of memory and attention and affects neural activity in various brain regions. Here we instructed participants to report on the orientation of repeatedly presented Necker cubes with high (HA) and low (LA) ambiguity. Manipulating the contrast of internal edges, we varied the ambiguity and orientation of the cube. We tested how both the repeated orientation (refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…31) However, the mechanistic details of symptoms such as wandering and becoming lost are not yet known. Maksimenko et al 32) reported that the precuneus and parahippocampal gyrus were active while deciding the orientation of the Necker cube under a priming condition. Therefore, in AD, low scores on the CCT and impaired route finding may have the same neural basis.…”
Section: Discussionmentioning
confidence: 99%
“…31) However, the mechanistic details of symptoms such as wandering and becoming lost are not yet known. Maksimenko et al 32) reported that the precuneus and parahippocampal gyrus were active while deciding the orientation of the Necker cube under a priming condition. Therefore, in AD, low scores on the CCT and impaired route finding may have the same neural basis.…”
Section: Discussionmentioning
confidence: 99%
“…In the pairwise comparison, critical a -level was set to 0.05, while in the cluster-level statistics, it was set to 0.025, which corresponded to a 0.05 false alarm rate in a two-sided test. Finally, the minimal number of the elements in the cluster was set to 2, and the number of permutations was equal to 2000 [ 35 , 36 ]. This number of permutations was sufficient since it was empirically found that their increase does not change the results obtained for the considered problem.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction time (group mean) was 0.84 s for LA and 1.09 s for HA stimuli (Figure 2C). This simplification is based on our previous works on the Necker cube images [7,25]. It enables revealing effects of ambiguity and provides a sufficient number of trials to minimize additional effects of orientation, a bias of the presentation moment, and the previously presented stimulus [7].…”
Section: Behavioral Estimatesmentioning
confidence: 99%
“…This simplification is based on our previous works on the Necker cube images [7,25]. It enables revealing effects of ambiguity and provides a sufficient number of trials to minimize additional effects of orientation, a bias of the presentation moment, and the previously presented stimulus [7]. Simultaneously, according to Brunye et al, very different perceptual and cognitive processes may underlie decision making at low, medium, and high uncertainty levels [15].…”
Section: Behavioral Estimatesmentioning
confidence: 99%
See 1 more Smart Citation